The model of decision making support system for detection and assessment of the state information security threat of social networking services - Молодецька-Гринчук, Катерина Валеріївна (Ukrainian Scientific Journal of Information Security, 2017)
Social networking services represent progressive the communication medium of participants of the virtual communities named actors. In case of distribution in the virtual communities doubtful, incomplete or the distorted content social networking services turn into the effective instrument of holding the information actions directed to manipulation with public opinion, influence on freedom of choice, distribution of appeals to separatism and etc. Therefore there is a need for development the model of decision making support system for detection of the country's information security threat of social networking services and assessment of their level. Controls for support of controlled transition of the virtual community to the given status of information security are the basis for the offered model methods of the of detecting partial signs of information actions in social networking services, the non-linear diagram of compromises for an assessment of signs of threats and synergy. As a result of functioning of decision making support system the recommended decisions are made for counteraction to the revealed threats. Depending on the sphere of public work which the threat influences appropriate public executive bodies carry out actions for its neutralization. Thus efficiency is reached, also high-speed performance of system of support of information security of the state in social networking services is effective.